A novel chimeric dengue vaccine candidate composed of consensus envelope protein domain III fused to C-terminal-modified NS1 protein. Issue 15 (1st April 2022) - Huang, Hong-Jyun; Yang, Martyr; Chen, Hsin-Wei; Wang, Shuying; Chang, Chih-Peng; Ho, Tzong-Shiann; Kao, Yu-San; Tien, Sen-Mao; Lin, Hsing-Han; Chang, Po-Chun; Lai, Yen-Chung; Hsiao, Yu-Peng; et al.
Abstract: There is an urgent need for a safe and effective vaccine against dengue virus (DENV) which infects about 390 million humans per year. In the present study we combined modifications of two DENV proteins, the nonstructural protein 1 (NS1) and the envelope (E) protein, to produce a DENV vaccine candidate with enhanced features. One of these modified proteins was a C-terminal-deleted fragment of NS1 called ΔC NS1 which we have shown previously to be protective without the potentially harmful effects of cross-reactive epitopes common to surface antigens on platelets and endothelial cells. The other modified protein was an envelope protein domain III (cEDIII) containing a consensus amino acid sequence among the four serotypes of DENV, which induces neutralizing antibody against all four DENV serotypes. The cEDIII and ΔC NS1 were expressed as a fusion protein cEDIII-ΔC NS1 and its protective effects against DENV were evaluated in a mouse model. C3H/HeN mice were immunized three times with cEDIII-ΔC NS1 fusion protein mixed with alum as adjuvant. Sera collected from cEDIII-ΔC NS1-immunized mice neutralized four serotypes of DENV and also caused complement-mediated cytolysis of HMEC-1 cells infected with each of the four different DENV serotypes. Mice immunized with cEDIII-ΔC NS1 and challenged with DENV showed reduced serum virus titer, soluble NS1 and bleeding time, compared with mice infected with DENV alone. The results reveal that antibodies induced by cEDIII-ΔC NS1 not only show anti-viral efficacy by in vitro assays but also provide protective effects against DENV infection in a mouse model. The cEDIII-ΔC NS1 thus represents a novel, effective DENV vaccine candidate.